2017
DOI: 10.1093/infdis/jix409
|View full text |Cite
|
Sign up to set email alerts
|

Key Factors Influencing the Emergence of Human Immunodeficiency Virus Drug Resistance in Low- and Middle-Income Countries

Abstract: The emergence and spread of human immunodeficiency virus (HIV) drug resistance from antiretroviral roll-out programs remain a threat to long-term control of the HIV-AIDS epidemic in low- and middle-income countries (LMICs). The patterns of drug resistance and factors driving emergence of resistance are complex and multifactorial. The key drivers of drug resistance in LMICs are reviewed here, and recommendations are made to limit their influence on antiretroviral therapy efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 59 publications
1
20
0
Order By: Relevance
“…KEYWORDS HIV, SIV, animal models, dolutegravir, resistance D espite the increasing arsenal of potent antiretroviral drugs (ARV) and combinations to combat human immunodeficiency virus (HIV) infection, the emergence of viral mutants with reduced susceptibility (drug resistance) remains a major concern. This is especially the case for middle-and low-income countries, where factors such as late presentation, an inconsistent supply chain, poor adherence, suboptimal drug regimens, and a lack of routine viral load monitoring contribute to ongoing virus replication, which promotes the emergence and persistence of such drug-resistant mutants (1).…”
mentioning
confidence: 99%
“…KEYWORDS HIV, SIV, animal models, dolutegravir, resistance D espite the increasing arsenal of potent antiretroviral drugs (ARV) and combinations to combat human immunodeficiency virus (HIV) infection, the emergence of viral mutants with reduced susceptibility (drug resistance) remains a major concern. This is especially the case for middle-and low-income countries, where factors such as late presentation, an inconsistent supply chain, poor adherence, suboptimal drug regimens, and a lack of routine viral load monitoring contribute to ongoing virus replication, which promotes the emergence and persistence of such drug-resistant mutants (1).…”
mentioning
confidence: 99%
“…In contrast, other studies have found no association with treatment outcomes when low-frequency resistance mutations are detected that confer resistance to an ARV drug used in the regimen (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29). These conflicting results make interpretation of resistance results from newer, more sensitive resistance assays difficult (30).…”
Section: Introductionmentioning
confidence: 93%
“…Drug resistance is when the response to a drug in a susceptible parasite population decreases significantly [46]. According to studies by the WHO, it was found that in 2010 the prevalence of HIV drug resistance for patients starting treatment was 6.8% for any drug, and that the treatment of these patients was more likely to fail [47], [48]. Drug resistance leads to further challenges relating not only to the patient's own future treatment, but also to the whole community [25].…”
Section: Drug Resistancementioning
confidence: 99%